Evaluation of ambulatory electrocardiographic monitoring of patients after high-risk acute coronary syndrome: the MONITOR ACS-Epic 13 randomized trial - De La Torre Hernandez, Jose M.; Exposito, Victor; Gonzalez Enriquez, Susana; Rodriguez Entem, Felipe; Margarida, Adrian; García Camarero, Tamara; Veiga, Gabriela; Sainz Laso, Fermin; Lee, Dae-Hyun; Gil Ongay, Aritz; Barrera, Sergio; Catoya, Santiago; et al. (Frontiers in Cardiovascular Medicine, 2025)
AimsPatients with acute coronary syndrome (ACS) may experience adverse events during follow-up. Previous trials have shown that asymptomatic arrhythmias preceded these adverse events in a substantial proportion of patients. Ambulatory remote monitoring may allow early detection of electrocardiographic alterations with therapeutic and prognostic implications. This study aims to evaluate the efficacy of remote monitoring in this population.Methods and resultsThis is a single-center, randomized controlled trial designed to evaluate the efficacy of 12-month monitoring of high-risk patients after ACS. High risk was defined by a GRACE score over 118 and a CHA2DS2-VASc score over 2. In the intervention arm, two different systems were implemented: an implantable loop recorder in all patients and a portable mobile ECG system in those suitable. The primary endpoint was detection rates for atrial fibrillation/flutter, ventricular arrhythmias, and advanced conduction abnormalities. A total of 150 patients (estimated sample size) were included. Baseline clinical characteristics were comparable. The primary endpoint was achieved in 21.3% of the patients in the monitoring group and only in 2.7% in the control group (p = 0.0005). The combined diagnosis of atrial fibrillation/flutter was significantly more frequent in the monitoring group (10.6% vs. 1.3%, p = 0.016). The incidence of death, myocardial infarction, or stroke at 12 months was 9.3% in the control group and 5.3% in the monitoring group (p = 0.34).ConclusionsAmbulatory monitoring of high-risk patients after ACS shows a significantly higher detection of ECG-clinically relevant findings as compared with a control group. This was not translated into a difference in 1-year MACE, though the study was clearly underpowered for these clinical endpoints.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT03940066?tab=history&a=3NCT03940066, identifier: NCT03940066.